Preparation and In Vitro Evaluation of a Gadolinium-Containing Vitamin E TPGS Micelle as a Potential Contrast Agent for MR Imaging - Yongkang Gai; Yuying Li; Shuangping Wu; Ling Xu; Yao Lu; Xiaoli Lan; Guangya Xiang; Xiang Ma (MDPI AG, 2023)
The application of many currently evaluated macromolecular contrast agents for magnetic resonance imaging (MRI) has been limited because of their bio-incompatibility and toxicity. The aim of this study is to synthesize and characterize a new micelle-based TPGS gadolinium chelate as a biocompatible MRI contrast agent for prolonged blood circulation time and good tumor imaging contrast. The TPGS-gadolinium conjugate was prepared through the conjugation between TPGS-SA and bifunctional L-NETA-Gd chelate. The conjugate was characterized with regard to molecular weight, critical micellar concentration and particle sizes, cellular uptake, and in vitro cell MRI. Distributions of the MRI contrast agent in various organs were determined via intravenous injection of the agent into mice bearing xenograft tumors. The successfully prepared TPGS-L-NETA-Gd micelle exhibited improved cellular uptake in HepG2 cells and xenografts and high in vivo safety. Distributions of TPGS-L-NETA-Gd in mice showed enhanced cellular uptake up to 2 h after the contrast agent injection. Its in vitro and in vivo properties make it a favorable macromolecular MRI contrast agent for future in vivo imaging.